(untitled) (Western European Journal of Medicine and Medical Science, 2024)
In studies, 1-(4¢-methoxyphenyl)-6,7-dimethoxy-1,2,3,4-tetrahydroisoquinoline (F-4) and 6,7- dimethoxy-1,2,3,4-tetrahydroisoquinoline (F-36 ) cardioprotective properties of alkaloids were studied. In this case, cardiomyocyte Ca 2+ -transport systems in the presence of their specific inhibitors were carried out under hypoxia conditions. Blockers of potential-dependent Ca2+ - channels, such as nifedipine and Na+ /Ca2+ - exchange blockers such as NiCl2 were used. The purpose of this study is to evaluate the cardioprotective properties of F-4 and F-36 isoquinoline alkaloids under hypoxia conditions in vitro and to expand the understanding of hypoxia-related molecular signaling pathways